2004
DOI: 10.1177/0115426504019006563
|View full text |Cite
|
Sign up to set email alerts
|

The Acute Respiratory Distress Syndrome: Role of Nutritional Modulation of Inflammation Through Dietary Lipids

Abstract: The acute respiratory distress syndrome (ARDS) is the most serious form of acute hypoxic respiratory failure. ARDS represents the expression of an acute, diffuse, inflammatory process in the lungs consequent to a variety of infectious and noninfectious conditions. It is characterized pathologically by damage to pulmonary epithelial and endothelial cells, with subsequent alveolar-capillary leak and exudative pulmonary edema. The main clinical features of ARDS include rapid onset of dyspnea, severe defects in ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 72 publications
0
6
0
4
Order By: Relevance
“…As n -3 fatty acids compete with n -6 fatty acids in the synthetic pathway for pro-inflammatory eicosanoids, providing the correct ratio of fatty acid types may also be important. Mizock ( 47 ) suggested an optimum ratio of 1:2 n -6 to n -3 whereas other authors have suggested 1:3 ( 46 ) . While clearly some n -6 fatty acids are essential, they are pro-inflammatory and another way of possibly reducing the amount in enteral feeds would be to substitute some of the long-chain TAG for medium-chain TAG.…”
Section: N-3 Fatty Acidsmentioning
confidence: 99%
“…As n -3 fatty acids compete with n -6 fatty acids in the synthetic pathway for pro-inflammatory eicosanoids, providing the correct ratio of fatty acid types may also be important. Mizock ( 47 ) suggested an optimum ratio of 1:2 n -6 to n -3 whereas other authors have suggested 1:3 ( 46 ) . While clearly some n -6 fatty acids are essential, they are pro-inflammatory and another way of possibly reducing the amount in enteral feeds would be to substitute some of the long-chain TAG for medium-chain TAG.…”
Section: N-3 Fatty Acidsmentioning
confidence: 99%
“…EPA and DHA anti-inflammatory mechanisms include: 1) removal of arachidonic acid from the phospholipid nucleus of inflammatory cell membranes, reducing the production of pro-inflammatory substance; 2) inhibition of synthesis of pro-inflammatory eicosanoids by competition with arachidonic acid in cyclooxygenase and lipoxygenase enzymes; 3) reduction of platelet and leukocyte adhesion in the endothelium; 4) inhibition of inflammatory gene expression; 5) reduction of oxidative lesions by stimulation of glutathione production; 6) improvement of anti-inflammatory resolvin synthesis; 7) a protective lung effect mediated by the reduction of the release of inflammatory mediators derived from the intestine in mesenteric lymphatic vessels and the thoracic duct (Glatzle et al, 2007;Mizock & DeMichele, 2004;Serhan, Arita, Hong, & Gotlinger, 2004).…”
Section: ω-3 Fatty Acidsmentioning
confidence: 99%
“…Several of these metabolites, thromboxane A 2 , leukotrienes, and prostaglandin E 2 , have been implicated in the development of acute lung injury. 27,33,34 A specialized enteral formula is available to potentially modulate this inflammatory cascade. The enteral formula offers a modified lipid component containing borage and fish oils, sources of eicosapentaenoic acid (EPA) and γ-linolenic (GLA) acid.…”
Section: Enteral Nutrition Modification In Ardsmentioning
confidence: 99%
“…Vasoconstriction, platelet aggregation, and neutrophil accumulation are reduced when the eicosanoid balance favors anti-inflammatory rather than proinflammatory mediators. 33,36 The specialized enteral formula provides a greater amount of total lipid than do other formulas designed for metabolic stress. Approximately 55% of total calories are provided as lipid compared with a range of 30% to 39% for other metabolic enteral formulas.…”
Section: Enteral Nutrition Modification In Ardsmentioning
confidence: 99%